Photothermal analysis of heterogeneous semiconductor structures under a pulse laser irradiation - Burbelo, R.; Isaiev, M.; Kuzmich, A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
The analysis of photothermal conversion in materials with modified properties of surface layer was made in this work. Influence of both physical and geometrical nonlinearities on the process of heat distribution was estimated.